Preparation of phosphogypsum ecological concrete and study on its phytogenic properties - Liu, Rongxin; Liu, Chunduo; Du, Jiang; Wang, Cheng; Yuan, Yonghui; Zhang, Xin (Frontiers in Environmental Science, 2025)
In this study, vegetative eco-concrete was prepared based on electrolytic manganese slag/phosphogypsum composite cementitious material as binder and clayey ceramic grains as aggregate. Based on the conditions of porosity and water-cement ratio, the optimal proportion of phosphogypsum-based eco-concrete was investigated, and concrete specimens with good performance were prepared (14 days compressive strength: 3.49 MPa, permeability coefficient: 1.37, total porosity: 24.5%, Improved compressive strength by 15% and water retention by 20%). The nutrient matrix of vegetative eco-concrete with different phosphogypsum/electrolytic manganese slag ratios was designed and modified, and the vegetative performance of the eco-concrete was investigated using four-season grass, ryegrass, clippings and clover as the grass species. The results showed that the eco-concrete based on phosphogypsum as raw material was rich in nutrients such as nitrogen, phosphorus and potassium, which could meet the requirements of plant growth, Supporting plant growth with a 30% increase in root length and 25% improvement in biomass compared to control concrete. The addition of improvers had a good passivation effect on heavy metals such as As, Cu, Cr, Zn, Sb and Pb in the phytogenic substrate. The adaptability of different grass species to the planting substrate was Four Seasons > ryegrass > shepherd’s purse > clover, alfalfa, dogbane; the application of electrolytic manganese slag substrate had the best performance of planting, and the planting substrate with the application of improver inhibited the growth of plants. The study addresses the challenge of using phosphogypsum as a binder in concrete, which has traditionally faced issues with strength and stability. By optimizing the mix ratio and curing process, we were able to achieve a concrete material that not only performs well mechanically but also supports plant growth.